Trends in maternal characteristics and perinatal outcomes among Japanese pregnant women with type 1 and type 2 diabetes from 1982 to 2020. Issue 10 (31st May 2022) - Fujikawa Shingu, Kei; Waguri, Masako; Takahara, Mitsuyoshi; Katakami, Naoto; Shimomura, Iichiro
Abstract: Aims/Introduction: This study investigated the time trends of the maternal characteristics and perinatal outcomes of Japanese pregnant women with diabetes. Materials and Methods: This retrospective study included 621 deliveries in 429 Japanese women with diabetes between 1982 and 2020. The association of the delivery date with clinical features was analyzed using the generalized estimating equations to adjust for the within‐person correlation. Results: The mean age of delivery and the mean diabetes duration increased over time (both P  < 0.001), while the prevalence of diabetic retinopathy decreased ( P  = 0.006). The mean HbA1c values during pregnancy decreased significantly over time (all P  < 0.001). The decreasing trends were associated with preterm delivery ( P  = 0.021) but not with other perinatal outcomes. The time trends were significantly different between patients with type 1 diabetes mellitus and with type 2 diabetes mellitus in large for gestational age (LGA) and stillbirth (both P for interaction <0.05). The rate of LGA decreased among patients with type 2 diabetes ( P  = 0.003) but not those with type 1 diabetes ( P  = 0.413). In contrast, the prevalence of stillbirth was decreased among those with type 1 diabetes ( P  < 0.001) but not those with type 2 diabetes ( P  = 0.768). The proportion of major congenital anomalies did not change in the overall population ( P  = 0.259) and among patients with type 2 diabetes ( P  = 0.229), but it increased among those with type 1 diabetes ( P  = 0.044), although the difference between those with type 1 diabetes and type 2 diabetes was not statistically significant ( P for interaction = 0.166). Conclusions: Maternal glycemic control has improved over the decades, whereas the improvement of perinatal outcomes has been limited. Perinatal outcomes still need to be improved in Japanese women with diabetes.